Changing mortality in congenital heart disease - Khairy, Paul; Ionescu-Ittu, Raluca; Mackie, Andrew S; Abrahamowicz, Michal; Pilote, Louise; Marelli, Ariane J (Journal of the American College of Cardiology, 2010)
This study sought to characterize temporal trends in all-cause mortality in patients with congenital heart disease (CHD). Historically, most deaths in patients with CHD occurred in early childhood. Notable advances have since been achieved that may impact on mortality trends. We conducted a population-based cohort study of patients with CHD in Quebec, Canada, from July 1987 to June 2005. A total of 8,561 deaths occurred in 71,686 patients with CHD followed for 982,363 patient-years. The proportion of infant and childhood deaths markedly declined from 1987 to 2005, with a reduction in mortality that exceeded that of the general population. Distribution of age at death transitioned from a bimodal to unimodal, albeit skewed, pattern, more closely approximating the general population. Overall, mortality decreased by 31% (mortality rate ratio: 0.69, 95% confidence interval [CI]: 0.61 to 0.79) in the last (2002 to 2005) relative to the first (1987 to 1990) period of observation. Mortality rates decreased in all age groups below 65 years, with the largest reduction in infants (mortality rate ratio: 0.23, 95% CI: 0.12 to 0.47). In adults 18 to 64 years, the mortality reduction (mortality rate ratio: 0.84, 95% CI: 0.73 to 0.97) paralleled the general population. Gains in survival were mostly driven by reduced mortality in severe forms of CHD, particularly in children (mortality rate ratio: 0.33, 95% CI: 0.19 to 0.60), and were consistent across most subtypes. Deaths in CHD have shifted away from infants and towards adults, with a steady increase in age at death and decreasing mortality.